Engineering On‐Surface Spin Crossover: Spin‐State Switching in a Self‐Assembled Film of Vacuum‐Sublimable Functional Molecule. Issue 11 (22nd January 2018) - Kumar, Kuppusamy Senthil; Studniarek, Michał; Heinrich, Benoît; Arabski, Jacek; Schmerber, Guy; Bowen, Martin; Boukari, Samy; Beaurepaire, Eric; Dreiser, Jan; Ruben, Mario
Abstract: The realization of spin‐crossover (SCO)‐based applications requires study of the spin‐state switching characteristics of SCO complex molecules within nanostructured environments, especially on surfaces. Except for a very few cases, the SCO of a surface‐bound thin molecular film is either quenched or heavily altered due to: (i) molecule–surface interactions and (ii) differing intermolecular interactions in films relative to the bulk. By fabricating SCO complexes on a weakly interacting surface, the interfacial quenching problem is tackled. However, engineering intermolecular interactions in thin SCO active films is rather difficult. Here, a molecular self‐assembly strategy is proposed to fabricate thin spin‐switchable surface‐bound films with programmable intermolecular interactions. Molecular engineering of the parent complex system [Fe(H2 B(pz)2 )2 (bpy)] (pz = pyrazole, bpy = 2, 2′‐bipyridine) with a dodecyl (C12 ) alkyl chain yields a classical amphiphile‐like functional and vacuum‐sublimable charge‐neutral Fe II complex, [Fe(H2 B(pz)2 )2 (C12 ‐bpy)] (C12 ‐bpy = dodecyl[2, 2′‐bipyridine]‐5‐carboxylate). Both the bulk powder and 10 nm thin films sublimed onto either quartz glass or SiO x surfaces of the complex show comparable spin‐state switching characteristics mediated by similar lamellar bilayer like self‐assembly/molecular interactions. This unprecedented observation augurs well for the development of SCO‐based applications, especially in molecular spintronics. Abstract : Self‐assembly and spin crossover go hand in hand, leading to the realization of comparable spin‐state switching characteristics of a pseudoamphiphilic charge‐neutral and vacuum‐sublimable functional SCO complex in bulk and thin film states with implications for the development of large‐area spintronics devices based on SCO complexes.